A Novel Non-Immunoglobulin (non-Ig)/BCL6 Translocation in Diffuse Large B-Cell Lymphoma Involving Chromosome 10q11.21 Loci and Review on Clinical Consequences of BCL6 Rearrangements - Jarosova, Marie; Kriegova, Eva; Schneiderova, Petra; Fillerova, Regina; Prochazka, Vit; Mikesova, Michaela; Flodr, Patrik; Indrak, Karel; Papajik, Tomas (Pathology oncology research, 2016)
BCL6 rearrangements (3q27) are the most common chromosomal abnormalities in diffuse large B-cell lymphoma (DLBCL), with numerous immunoglobulin (Ig) and non-Ig genes as partners. In DLBCL, the translocations occur predominantly in the "major breakpoint region" encompassing the first noncoding exon and a part of the first intron of BCL6; few cases with "alternative breakpoint cluster" located 245-285 kb 5' BCL6 were also described. The regulatory sequences of known Ig and non-Ig partners replace the 5' untranslated region of the BCL6 in the same transcriptional orientation. Contrary to Ig/BCL6 fusions typical by high BCL6 gene expression, in non-Ig/BCL6 translocations were observed unexpectedly low BCL6 mRNA levels. From the clinical point of view, the survival rate of DLBCL patients with non-Ig partners is inferior to those with Ig/BCL6 translocations, suggesting that non-Ig/BCL6 fusion is a poor prognostic indicator. Hereby we provide comprehensive information about known non-Ig translocation partners and clinical consequences of BCL6 rearrangements in DLBCL. Moreover, we describe a novel reciprocal translocation t(3;10) in refractory patient with DLBCL with the breaking points at 5' untranslated region of BCL6 and 5' untranslated region of the RASGEF1A gene on chromosome 10q11.21 loci; this rearrangement was associated with low BCL6 and RASGEF1A gene expressions. Our patient harbouring dual chromosomal rearrangement involving BCL2 and BCL6 genes relapsed three-times and died soon; thus, further supporting the notion that non-Ig/BCL6 fusion is a poor prognostic indicator of DLBCL. There is evidence of prognostic value of BCL6 rearrangements also in rituximab era.
Keywords: BCL6 rearrangements; difúzní velkobuněčný B-lymfom; genová přestavba; Prognosis; protoonkogenní proteiny c-bcl-6; Middle Aged; mužské pohlaví; Lymphoma, Large B-Cell, Diffuse; Gene Rearrangement; BCL2 rearrangements; prognóza; Humans; Chromosomes, Human, Pair 10; lidé středního věku; Complex chromosomal changes; Translocation, Genetic; Diffuse large B-cell lymphoma; Proto-Oncogene Proteins c-bcl-6; translokace genetická; Non-immunoglobulin gene translocations; lidé; Male; lidské chromozomy, pár 10